2020
DOI: 10.1038/s41398-020-01050-7
|View full text |Cite
|
Sign up to set email alerts
|

Translational study of the whole transcriptome in rats and genetic polymorphisms in humans identifies LRP1B and VPS13A as key genes involved in tolerance to cocaine-induced motor disturbances

Abstract: Motor disturbances strongly increase the burden of cocaine use disorder (CUDs). The objective of our translational study was to identify the genes and biological pathways underlying the tolerance to cocaine-induced motor effects. In a 5-day protocol measuring motor tolerance to cocaine in rats (N = 40), modeling the motor response to cocaine in patients, whole-genome RNA sequencing was conducted on the ventral and dorsal striatum to prioritize a genetic association study in 225 patients with severe CUD who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…While VPS13A seems not to be a core synaptic protein, previous studies suggested that VPS13A was modulated by the dopaminergic system [ 25 ]. Thus, we explored if VPS13A expression was modulated by the manipulation of specific neurotransmitter systems.…”
Section: Resultsmentioning
confidence: 99%
“…While VPS13A seems not to be a core synaptic protein, previous studies suggested that VPS13A was modulated by the dopaminergic system [ 25 ]. Thus, we explored if VPS13A expression was modulated by the manipulation of specific neurotransmitter systems.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have employed smaller numbers of animals, used inbred strains that were selectively bred to be high or low responders (52) and used the BXD recombinant inbred mouse panel (53) or Hybrid Mouse Diversity Panel (HMDP) (54). Moreover, several of these studies also used other proxies for addiction-like behaviors, like exploratory locomotion (52) or drug-induced motor effects (55) following passive drug injections.…”
Section: Discussionmentioning
confidence: 99%
“…The results from these studies might provide valuable information on the genetic behind individual differences in the vulnerability and resilience to oxycodone abuse and might also provide several addiction-like traits to be used for personalized diagnoses and/or novel treatment approaches. Finally, to facilitate investigating the biological origins of the difference in oxycodone addiction-like behaviors through epigenetic, transcriptomic (55), microbiome, neurobiological, or other mechanisms in HS rats beyond genetic factors, samples of these behavioral and genetically characterized animals were collected and made available free of charge through the oxycodone biobank (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an experimental model, locomotor sensitisation is linked with increased tendency to self-administer psychostimulants [ 92 , 93 ] and with reinstatement of previously extinguished self-administration [ 94 , 95 ]. Whereas the existence of psychomotor sensitisation in humans is discussed [ 96 , 97 ], it is a key aspect of vulnerability to drug addiction and relapse, specifically drug craving or compulsive drug-seeking behaviour [ 91 , 98 , 99 ]. Still, locomotor sensitisation can be dissociated from the rewarding effect of a drug of abuse and conditioned place preference or self-administration are more appropriate experimental paradigms to test this aspect [ 100 102 ].…”
Section: Converging Actions On Brain Reward Pathway Elicit Its Remodellingmentioning
confidence: 99%